Soil hydraulic properties affected by topsoil thickness in perennial biofuel and row crop management - Zaibon, Syaharudin; Anderson, Stephen H.; Kitchen, Newell R. (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Conversion to perennial biofuel production systems from annual row crop systems can restore soil properties, however there are inadequate information about these influences. The aim of this study was to evaluate the effect of topsoil thickness on hydraulic properties in claypan soil for corn-soybean crops and switchgrass (Panicum virgatum L.) production systems. The experiment was carried out at the Soil Productivity Assessment for Renewable Energy and Conservation (SPARC) plots at the University of Missouri South Farm Research Center. Plots were recreated in 2009 with four levels of topsoil thickness (4, 11, 22, and 36 cm) on a Mexico silt loam (Vertic Epiaqualfs). Every plot was planted with either switchgrass or a corn-soybean rotation. Results showed that soil under switchgrass had 53 and 27% higher macroporosity (>1000 μm diameter) and coarse mesoporosity (60–1000 μm diameter), respectively, than row crop management. This caused 73% greater Ksat and 11% higher water content at saturation than corn-soybean management. switchgrass planted on degraded soil (shallow topsoil treatment) resulted in greater Ks (estimated saturated hydraulic conductivity), S (sorptivity), qs (quasi-steady infiltration rate) and Kfs (field-saturated hydraulic conductivity) values than with row crop management for both 2014 and 2015 measurement years. Switchgrass is suggested to be planted on degraded claypan landscapes for improved water use.